A STUDY OF THE PRESSING ISSUES IN THE DEVELOPMENT OF ATHLETICS IN CONTEMPORARY SPORTS - Temur Palvaniyazov Ametjanovich (Bright Mind Publishing, 2025)
The issues of developing athletics in modern sports are very relevant today. Athletics, with its diverse types and techniques, is one of the oldest and most popular sports, which is important not only for physical activity, but also for spiritual and social development. This article provides information on the current issues of developing athletics, their solutions and future prospects.
Keywords: athletics, sport, technical skills, sports grounds, training bases, sports infrastructure, mass media.